GAMBARAN KADAR UREUM DAN KREATININ PENDERITA PENYAKIT GINJAL KRONIK (PGK) YANG TERINFEKSI MALARIA DI RUMAH SAKIT UMUM DAERAH JAYAPURA - sabakthani kayoi; Ni Putu Rahayu Artini; I Wayan Tanjung Aryasa (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2020)
The aim of the study was to see the comparison of urea and creatinine levels in chronic kidney disease patients between those infected with malaria and those not infected with malaria at the Jayapura Regional General Hospital. This type of research is retrospective analytic. The samples of this study were chronic kidney patients who were infected with malaria and conducted an examination at the Jayapura Regional General Hospital that met the inclusion criteria, in order to obtain 30 positive malaria samples. The average urea level of female CKD patients infected with malaria was 116.7 mg/dL, the lowest was 63,8 mg/dL and the highest was 136,2 mg/dL. The average urea level of male CKD patients infected with malaria was 95,9 mg/dL, the lowest was 33.4 mg/dL and the highest was 231,0 mg/dL. The result of the mean creatinine level of female CKD patients infected with malaria was 17,5 mg/dL, the lowest was 9,92 mg/dL and the highest was 31,38 mg/dL. While the mean creatinine level of male CKD patients infected with malaria was 12,0 mg/dL, the lowest was 3,49 mg/dL and the highest was 26,27 mg/dL.